Integrin expression and adhesivity to fibronectin in primary acute myeloid leukemia cells: Impact of NPM1 and FLT3 mutations - Kuželová, Kateřina; Obr, Adam; Marková, Jana; Gašová, Zdenka (European journal of haematology, 2020)
OBJECTIVES: Interaction of leukemia cells with the bone marrow extracellular matrix promotes cell survival and resistance to chemotherapy. In this work, we analyzed integrin expression and adhesivity to fibronectin in primary cells from patients with acute myeloid leukemia. METHODS: Surface expression of integrins β1 and αVβ3 on primary leukemia cells (N = 46) was correlated with the stem cell marker CD34, as well as with cell adhesivity to fibronectin. The results were analyzed with regard to the mutational status of NPM1 and FLT3 genes. RESULTS: The integrin β1 was omnipresent, whereas αVβ3 was often more expressed on CD34-positive cells. In particular, higher αVβ3 expression on CD34+ cells was associated with NPM1 mutation (P = .0018). Monocytic leukemias had significantly higher αVβ3 expression compared to less maturated cases (P = .0008). Cells from patients with internal tandem duplications in FLT3 (FLT3-ITD) had lower adhesivity to fibronectin compared to cells with wild-type FLT3 (P = .031), specifically in less differentiated myeloblasts. Inhibition of a putative FLT3-ITD target, EZH2, increased cell adhesivity in MV4-11 cell line (P = .024). CONCLUSIONS: The integrin αVβ3 is expressed in particular on CD34+ cells with NPM1 mutation and might have a prognostic value in patients with mutated NPM1. FLT3-ITD is associated with lower cell adhesivity, especially in patients with less differentiated leukemias.
Keywords: CD34; jaderné proteiny; nádorové buněčné linie; Nucleophosmin; integrin; Cell Adhesion; Protein Binding; Nuclear Proteins; duplikace genu; integriny; Cell Membrane; fms-Like Tyrosine Kinase 3; fibronektiny; mutace; Leukemia, Myeloid, Acute; Cell Line, Tumor; AML; Gene Duplication; FLT3-ITD; Gene Expression; Fibronectins; Mutation; Humans; Fms-like tyrosine kinase; vazba proteinů; nukleofosmin; akutní myeloidní leukemie; buněčná membrána; tyrosinkinasa 3 podobná fms; exprese genu; buněčná adheze; lidé; Integrins